2016
DOI: 10.1002/jbio.201500256
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the differentiation ofex vivonerve and fat tissues using laser-induced breakdown spectroscopy (LIBS): Prospects for tissue-specific laser surgery

Abstract: In the present study, the elemental compositions of fat and nerve tissue during their plasma mediated laser ablation are studied in the context of tissue differentiation for laser surgery applications by using Laser‐Induced Breakdown Spectroscopy (LIBS). Tissue samples of porcine fat and nerve were prepared as ex vivo experimental objects. Plasma mediated laser ablation is performed using an Nd : YAG laser in open air and under normal stray light conditions. The performed measurements suggest that the two tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…In addition, a molecular line of carbon to nitrogen bonding (CN) was observed in the recorded spectra. The observed lines were in agreement with the lines described in literature [26][27][28][29][30][31][32][33][34]. Later on, based on the 22 chosen peak intensities, 231 intensity ratios were generated using permutation…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, a molecular line of carbon to nitrogen bonding (CN) was observed in the recorded spectra. The observed lines were in agreement with the lines described in literature [26][27][28][29][30][31][32][33][34]. Later on, based on the 22 chosen peak intensities, 231 intensity ratios were generated using permutation…”
Section: Discussionsupporting
confidence: 86%
“…Authors have recently shown that LIBS feedback systems for laserosteotomy could help surgeons avoid carbonizing bone [18]. Moreover, LIBS has shown its potential to differentiate between healthy and carious teeth [27,28], bone and spinal cord [29,30], bone and cartilage [31], nerve and fat [32], as well as nerve and gland [33]. Laserosteotomes connected to such a feedback system are so-called smart laserosteotomes [34].…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy analysis was applied for determination of lipid droplet content, distribution and saturation level in mice . Investigation of the differentiation of ex vivo nerve and fat tissues using laser‐induced breakdown spectroscopy was also done . All these powerful optical techniques are prospective for monitoring of tissue‐specific laser surgery, including liposuction.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the urgent problems of aesthetic surgery, which is to develop an effective and safe method of removing unwanted fat, remains unresolved. There are many contemporary wave‐based methods of fat cell lipolysis and liposuction, such as ultrasonic , radiofrequency and laser technologies. The wave method is associated with radiation in a certain range of wavelengths (frequencies), which is effectively absorbed by the tissue, that is, optical, microwave or ultrasonic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…LIBS feedback systems for laserosteotomy could help surgeons avoid cutting a wrong tissue or make it carbonized [1][2][3][4][5][6][7][8][9]. Laserosteotomes connected to such a feedback system are so-called smart laserosteotomes [10].…”
Section: Introductionmentioning
confidence: 99%